Mercury-resistant biofilm-forming bacteria and local plants in phytoremediation of small-scale gold mine tailings in Lombok Island, Indonesia - Siska Nurfitriani; Endang Arisoesilaningsih; Yulia Nuraini (Journal of Degraded and Mining Lands Management, 2023)
Small-scale gold mining is one of the sectors that contribute to the world's largest mercury contamination through the tailings it produces. Many efforts have been made to reduce mercury concentrations from tailings, one of which is by utilizing a combination of plants and bacteria. This study aims to analyze the combination of mercury-resistant biofilm-forming bacteria and local plants in the phytoremediation of small-scale gold mine tailings. This study used ten plant species divided into three groups and three biofilm-forming mercury-resistant bacteria (Bacillus toyonensis, Burkholderia cepacia, and Microbacterium chocolatum). Parameters observed included plant biomass, total chlorophyll, plant mercury content and media. The results showed that adding bacteria to each plant in the treatment had a different effect. Some plants with the addition of biofilm-forming bacteria had a higher wet weight than others. However, the addition of bacteria was not effective in increasing plant dry weight. The combination of biofilm-forming bacteria in the first and second plant groups reduced tailings mercury concentrations better than without the addition of bacteria. The combination of plants and bacteria in the third group gave higher media and plant mercury concentrations. This study shows that the addition of biofilm-forming bacteria can lead to increased remediation by plants. The second plant group treatment with a combination of P. indica, P. conjugatum, and S. sesban plants was the most effective in reducing tailings mercury content.